Manifestation of Atithi Devo Bhavah maxim on Sri Lankan Tamil refugees treatment in India - Maneesh Panakkeel; Aicha El Alaoui (Universitas Trunojoyo Madura, 2020)
This study discusses the reflection of Indian’s Athithi Devo Bhava policy towards Sri Lankan Tamil refugees during the hostility staged in the island since 1983. The enduring Indian practices of tolerance and goodwill resulted in following a benevolent policy towards all those who sought asylum. In ancient India, there were four cultural maxims: (1) Matru Devo Bhava, your mother is like God; (2) Pitru Devo Bhava, your father is like God; (3) Acharya Devo Bhava, your teacher is like God, and (4) Athithi Devo Bhava, your guest is like God. The refugee has considered as an Athithi (guest) to the country and treated them as God. India has accorded asylum to more than 25 million people in spite of the absence of strong refugee laws, but the treatment has been given on an ad hoc basis. The study is descriptive in nature. The information was collected from secondary sources. It underlines that the Indian government has been providing accommodation, food, and security to refugees. Subsequently, the services enjoyed by the Indian citizens are extended to refugees. There is a harmony between Sri Lankan Tamils and Indian Tamils in language and culture. Tamils in India and the Indian government has treated the refugee as a guest.